2015
DOI: 10.18178/ijmmm.2016.4.4.263
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric Polarization Enhancement of Thermoplastic Elastomers for Sensing and Energy Harvesting Applications

Abstract: Nano-structured dielectric thermoplastic elastomers (DTEs) such as poly(styrene-co-ethylene-co-butylene-styrene) [SEBS] and poly(styrene-co-ethylene-co-butylene-styrene)-grafted-maleic anhydride[SEBS-g-MA] triblock co-polymers have been shown to have superior mechanical performances relative to conventional dielectric elastomers such as silicones because of their morphology; which comprises of continuous hard and soft block copolymers and physical cross-linking between same. However, historically their use in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…This interaction promoted the interfacial polarization and, then, increased the dielectric permittivity. Similar results have been achieved by other authors using SEBS grafted with anhydride maleic (SEBS-g-MA) [36]. Other authors have observed a similar behavior when the BaTiO3 particles are coated with dopamine and dispersed in silicone rubber [37].…”
Section: Properties Of Sebs/batio 3 Composites Using Itaconic Acid As Compatibilizersupporting
confidence: 88%
“…This interaction promoted the interfacial polarization and, then, increased the dielectric permittivity. Similar results have been achieved by other authors using SEBS grafted with anhydride maleic (SEBS-g-MA) [36]. Other authors have observed a similar behavior when the BaTiO3 particles are coated with dopamine and dispersed in silicone rubber [37].…”
Section: Properties Of Sebs/batio 3 Composites Using Itaconic Acid As Compatibilizersupporting
confidence: 88%
“…The total dielectric permittivity of those samples was published in our previous work. 17 There was no significant difference between real dielectric permittivity shown in Figure 2 and Table 1 and total dielectric permittivity for all samples from our previous work because of low loss factor over the range of all frequency measured. However, total dielectric permittivity alone can't always give the information about the polarization capability of materials in all cases as it is the vector sum of loss factor and real dielectric permittivity.…”
Section: Resultsmentioning
confidence: 61%
“…7,16 Conductive fillers tend to change the dielectric permittivity of polymer matrices by several folds. 17 He and Tjong 18 reported the dielectric permittivity of polyvinylidene difluoride increased by 15 times with the addition 0.5% of reduced graphene sheets 19 . However, they also tend to increase the dielectric permittivity loss of nanocomposites leading such manufactured nanocomposites to have low dielectric strength.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of ceramic particles into PVDF matrix was demonstrated in [27,28], the dielectric constant increasing with increasing filler content. Typically, the 50 wt.% of ceramic fillers is the maximum of filler for obtaining films with suitable mechanical properties [29] while maximizing the dielectric response of the composite [30]. Neat PVDF and composites having 0.15, 0.25 and 4 wt.% CNTs and 50 wt.% BT were fabricated.…”
Section: Composite Preparationmentioning
confidence: 99%
“…With respect to SBS and SEBS, no relevant differences in the composites are observed for the addition of BT or CNT due to the fact when the CNT content is below the percolation threshold, the CNT does not form a conductive network and the nanocomposite is highly resistive, similar to BT nanocomposites. The dielectric constant increases with higher concentrations of both fillers as a result of the influence of particle distribution, polarization and interfacial polarization between the fillers and polymer matrix [30].…”
Section: Electrical Conductivity and Dielectric Propertiesmentioning
confidence: 99%